AB1103 NEUROLOGICAL IMPAIRMENT DURING SARCOIDOSIS. (June 2019) - sayhi, sameh; Dhahri, Rim; Boussetta, Najah; Arfaoui, Bilel; Laajili, Feida; Louzir, Bassem; Derbali, Hajer; Mrisa, Linda; Mrisa, Ridha
Abstract : Background: Objectives: To describe neurological impairment characteristics in sarcoidosis. Methods: This was a descriptive and retrospective study including 65 patients with sarcoidosis, followed in the departments of internal medicine and neurology at the Military Hospital of Tunis over a period of 20 years from 1997 to 2017. Results: A total of 65 patient files have been selected, of which 38 have neurological involvement. Thirty-eight patients met the inclusion criteria for Neurosarcoidosis. According to Zajicek's criteria, the diagnosis of neurosarcoidosis was certain in 2 cases, probable in 18 cases and possible in 18 cases. Neurological disorders were symptomatic in 58.5% of the studied population. Neurological signs were inaugural in 9 patients (14% of cases). A central neurological involvement was demonstrated in 33 patients (86.8%), the peripheral nervous system was affected in 5 patients (13.1%), and cranial nerve involvement was found in 10 patients (26.3%).%). Ten patients have had both central and peripheral impairement. Neurological involvement was significantly associated with cardiac, renal extra-thoracic, ophthalmologic, articular and cutaneous involvement (p <0.05) Genotyping of the conversion enzyme and HLA typing did not show any particular pattern of neurosarcoidosis in comparison with patients without neurological signs. Conclusion: Neurological impairement was frequently observed in our series. It was also significantly associated with multivisceral involvement without particular genetic pattern. Disclosure of Interests: None declared